11 Student aspih (SASPIH): a workshop in utilising social media as an educational tool. (17th November 2016) - Dalta, S; Shaw, S; Gopal, A
Abstract : Background: Healthcare systems rely on an ongoing culture of learning and improvement in order to remain up-to-date. As such, it is vital to explore different modes of education delivery in this technologically-orientated era that can overcome geographical boundaries, time constraints and cost-limitations, allowing a global community to participate in the learning experience. Social media is one such key modality. 1 The Association for Simulated Practice in Healthcare 2 student special interest group, Student ASPiH (sASPiH) 3 designed and held a workshop to empower undergraduates to utilise social media to teach. Methodology: A 1-hour workshop was held at the ASPiH annual conference in November 2015. It consisted of an interactive plenary discussing the various modalities of social media available, how to utilise them and ensure professionalism continued online, followed by a guided activity supporting participants to design their own educational intervention using social media. Participants completed pre and post-workshop questionnaires to assess the impact. Statistical analysis (student-t test) was performed on the data to assess educational value. Outcomes: Attendees demonstrated statistically and educationally significant changes in their attitudes towards social media as a learning tool. On a scale of 1 (not at all) to 7 (extremely), attendees felt more strongly that social media was useful (increase of 2.4, p = 0.004), and effective (+2.7, p < 0.001) in teaching healthcare professionals following the workshop. Additionally, they believed that using social media would be more enjoyable for students (+1.6, p = 0.005), and tutors (+1.3, p = 0.012). Finally, attendees indicated they were more likely to utilise social media in teaching (+2.1, p = 0.015). Impact: Social media is a powerful tool when used effectively. Our results suggest our workshop can inform and empower undergraduates to use social media to provide and engage with teaching opportunities online. References: Evans C. Twitter for teaching: Can social media be used to enhance the process of learning? Br J Educ Technol 2014;45 (5):902–915. ASPiH. Background [Internet]. ASPiH 2016. [Cited May 2016]. Available; http://www.aspih.org.uk/Background/ Gopal AA, Pendleton M, Cox DR. Creating Student ASPiH (sASPiH): Proposed business platform model – establishing a viable, resilient and accountable student branch of ASPiH. BMJ STEL 2014;1 (Suppl 1):A82–A83.